“A internet é o fio de nossas vidas”: influenciadores digitais na parceria entre C&A e o programa Big Brother Brasil - Bernardes, Mári Andrade (Universidade Federal de São Carlos, 2023)
Given the important role of fashion in the construction of social identities and the actual relevance of digital media, this dissertation aims to analyze how gender subjectivation processes take shape through fast-fashion discourses regarding digital influencers. Characterized by technological as well as social transformations, the digital age made it possible to create personal or corporative accounts in digital platforms. Consequently, corporate accounts started to post fashion images which enabled interaction through “comments” and “likes”. In this way, any personal account interested could engage interaction. Hence, the digital age became responsible for a major shift on gender and fashion related studies in the Sociology field, since it enabled different forms of interaction, sociability and subjectivity. Before the digital age, it was actually possible for some researchers to question to what extent traditional media really got through its public, since they barely seemed to be paying attention (given that they didn´t have the habit of commenting those contents). A completely different scenario seems to be on display nowadays, since the hundreds and thousands of likes and comments show an exact opposite behavior from that of the public back then. This certainly challenges the very questions some of these researchers posed before. Given this shift, in order to investigate its impact on the analysis proposed here initially, this dissertation takes @cea_brasil as its field site. More specifically, there were selected posts where, majorly, BBB21 participants were the main subjects. Methodologically, an incursion inspired by digital ethnography was conducted. Techniques such as participant and non-participant observation as well as semi-structured interviews were used. The interviews were conducted with those who either commented or liked the posts @cea_brasil. As theoretical references, there were taken into account authors who work from a foucaultian viewpoint, such as Judith Butler and Manuel Castells. As main results, the subjectivation processes were comprehended to destabilize the heterosexual power matrix from within the many tensions they dwell.
"The internet is the thread of our lives": digital influencers in the partnership between C&A and the television program Big Brother Brasil
Keywords: Moda fast-fashion; Processos de subjetivação de gênero; Influenciadores digitais; BBB21; C&A; Fast-fashion; Gender subjectivation processes; Digital influencers; BBB21; C&A; CIENCIAS HUMANAS::SOCIOLOGIA